DESIGN AND IMPLEMENTATION OF A NATIONAL E-LEARNING PLATFORM FOR BELARUS - Evans Dennison. J. (CV. Fahr Publishing, 2025)
The integration of e-learning systems at a national level has become a strategic priority in ensuring inclusive and resilient education, especially in the post-pandemic era. This study presents the design, development, and pilot implementation of a national e-learning platform tailored to the Belarusian context. Employing a design-based research (DBR) approach, the study progressed through four phases: needs assessment, system architecture, implementation, and evaluation. Mixed methods were used, including surveys (n=200), interviews, usability tests (SUS), and backend performance monitoring. Results show high system usability (SUS scores above 70), strong technical reliability (uptime > 97%), and increasing student engagement across pilot schools. Teachers reported improved planning, while students experienced greater access and autonomy in learning. The system’s modular architecture and cloud scalability ensure adaptability across diverse regions. In contrast to previously fragmented systems in Belarus, this platform enables centralized governance, pedagogical standardization, and data integration. The study contributes new insights into scalable digital education models in low- to middle-resource countries and aligns with global goals for equitable and quality education. This research also provides a replicable framework for other nations seeking to develop national digital learning infrastructures.